Project Work in Networked Distance Education - Knudsen, Morten; Helbo, Jan; Jensen, Lars Peter; Rokkjær, Ole; Borch, Ole; Østergaard, Jørgen (Proceedings of the International Conference on Networked Learning, 2000)
Project organized problem based learning is a successful concept for on-campus education at Aalborg University. Recently it has been the basis in networked distance education as well. This paper describes the experiences of Internet-mediated project work in a new Master of Industrial Information Technology education. For a pilot project, each student group prepared a report, evaluating the collaborative work process, and these process reports combined with the teachers observations, comprise the background material. The main conclusions are, that the project work was a strong learning motivation, enhancing peer collaboration, and that networked communication and face-to-face meetings was an efficient combination.